Improvement Model to increase production using forecasting tools and capability analysis at an Industrial Paints Manufacturing Plant - Balbin Reymundo, Ariana Xiomara (2023)
The global paint industry has a reach valued at $209.4 billion for this year. At the national level in Peru, this sector represents 1.27% of GDP, so this industry is of utmost relevance since the national per capita consumption is low, therefore, there is a great margin for improvement of this. This article describes the implementation of an improvement model that uses forecasting tools and capabilities coupled with a simulation to increase compliance with paint production, therefore; the central problem is analyzed using the VSM tool, in which the root causes, percentage of value-added and non-added time of the process are identified. After implementation, the model increased compliance with production orders by 26.86%, increased availability of resin input by 27.92, % and decreased cycle times by at least 2.5%.